Removal of phosphorus from water using calcium-rich organic waste and its potential as a fertilizer for rice growth - Lee, Jae In; Oh, Jung Seok; Yoo, Soo Cheul; Jho, Eun Hea; Lee, Chang Gu; Park, Seong Jik (Journal of Environmental Chemical Engineering, 2022)
Mussel shell (MS) waste was upcycled as value-added products, namely an adsorbent for P removal from lakes and P fertilizer after adsorbent use. Calcination improved the P adsorption capacity of MSs by changing the mineral structure from calcite (CaCO3) to lime (CaO) and portlandite (Ca(OH)2) and enhancing the elution amount of Ca2+. The MSs were calcined at the optimum calcination temperature of 800 °C (CMS-800) and then used to adsorb P in aqueous solution to form hydroxyapatite (Ca5(PO4)3(OH)). The pseudo-first-order and Langmuir models were well fitted to kinetic and equilibrium P adsorption by CMS-800. The maximum adsorption capacity of CMS-800 obtained from the Langmuir model was 66.70 mg/g. The adsorption amount of 88.40 mg/g at a pH of 3 decreased to 58.48 mg/g at a pH of 7, but increased again to 91.16 mg/g at a pH of 11. Anions coexisting in the P solution reduced the amount of P adsorbed by CMS-800; their effects were in the order of SO42- > HCO3- > > Cl- > NO3-. Two centimeters of CMS-800 in a fixed-bed column showed a P removal rate of 50.92% (4.29 mg/g) until saturation. The initial and final earthworm weights after the addition of CMS-800 and P-adsorbed CMS-800 (P-CMS-800) did not show a statistically significant difference. P-CMS-800 was present mainly in the form of Ca-bound P and residual P, which accounted for 43.07% and 55.64% of the total, respectively. The medium level of P-CMS-800 (0.73 g/kg soil) promoted plant growth by increasing major agronomic traits. CMS-800 can be used as an effective adsorbent to remove P from water, and P-CMS-800 can be used as a substitute for P fertilizer in rice cultivation.
Keywords: Adsorption capacities; Langmuir models; Mineral structure; Mussel shells; Organic wastes; P fertilizers; P removal; Portlandite; Rice growths; Value added products; Calcination; Fertilizer; Mussel shell; Phosphorus; Rice growth; Toxicity